A CSMA/CA based MAC protocol for hybrid Power-line/Visible-light communication networks: Design and analysis - Sheng Hao; Huyin Zhang; Fei Yang; Chenghao Li; Jing Wang (Digital Communications and Networks, 2024)
Hybrid Power-line/Visible-light Communication (HPVC) network has been one of the most promising Cooperative Communication (CC) technologies for constructing Smart Home due to its superior communication reliability and hardware efficiency. Current research on HPVC networks focuses on the performance analysis and optimization of the Physical (PHY) layer, where the Power Line Communication (PLC) component only serves as the backbone to provide power to light Emitting Diode (LED) devices. So designing a Media Access Control（MAC) protocol remains a great challenge because it allows both PLC and Visible Light Communication (VLC) components to operate data transmission, i.e., to achieve a true HPVC network CC. To solve this problem, we propose a new HPC network MAC protocol (HPVC MAC) based on Carrier Sense Multiple Access/Collision Avoidance (CSMA/CA) by combining IEEE 802.15.7 and IEEE 1901 standards. Firstly, we add an Additional Assistance (AA) layer to provide the channel selection strategies for sensor stations, so that they can complete data transmission on the selected channel via the specified CSMA/CA mechanism, respectively. Based on this, we give a detailed working principle of the HPVC MAC, followed by the construction of a joint analytical model for mathematical-mathematical validation of the HPVC MAC. In the modeling process, the impacts of PHY layer settings (including channel fading types and additive noise feature), CSMA/CA mechanisms of 802.15.7 and 1901, and practical configurations (such as traffic rate, transit buffer size) are comprehensively taken into consideration. Moreover, we prove the proposed analytical model has the solvability. Finally, through extensive simulations, we characterize the HPVC MAC performance under different system parameters and verify the correctness of the corresponding analytical model with an average error rate of 4.62% between the simulation and analytical results.